Vertical Alignment Design of Special Operational Road: A Case TPA Bangkonol, Banten - Sahara, Dwiki Ali; Rifai, Andri Irfan; Irianto, Muhammad Alamsyah (DAS Institute, 2022)
Infrastructure building is part of national development to provide services to the community. Road infrastructure development as an infrastructure for streamlined land transport. The problem with the current condition is that the operational road for access to waste disposal at the TPA Bangkonol is still in an unpaved road condition. The research mainly focuses on vertical alignment design. It is expected to get the results of efficient geometric design and meet the safety and comfort aspects. From the results of this study obtained vertical alignment calculation data, there are seven convex verticle curves and eight concave verticle curves on the operational road of TPA Bangkonol Pandeglang Regency. The technical design criteria for the design speed are 30km/hour. A maximum longitudinal grade value is 8% also a vertical Lmin is 18m. Geometric calculation of the TPA operational road based on the Highway Geometric Design Indonesia that can meet the safety and comfort aspects of drivers.